Metode Diagnosis Dan Tindakan Medis Pyometra Pada Anjing Poodle : Kasus Di Rumah Sakit Hewan Sumatera Barat - Riska Asria Sa'adatur Rahmi; Gito Haputra; Putri Utami (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2026)
Pyometra is a common reproductive disorder in intact female dogs characterized by the accumulation of purulent material within the uterus and may cause serious systemic complications if not treated promptly. This case report describes the diagnostic approach and clinical management of open pyometra in a female poodle dog treated at the West Sumatra Animal Hospital. A six-year-old intact female poodle was presented with a history of reddish vaginal discharge, fever, and abdominal distension. Diagnosis was established based on anamnesis, physical examination, ultrasonographic examination, and hematological analysis. Ultrasonography revealed uterine enlargement with hypoechoic fluid accumulation within the uterine lumen, while hematological examination showed leukocytosis and decreased packed cell volume. Based on these findings, the dog was diagnosed with open pyometra. Definitive treatment was performed by ovariohysterectomy under general anesthesia, followed by postoperative antibiotic, analgesic, and supportive therapy. Postoperative recovery was uneventful, and wound healing progressed well. This case highlights the importance of early diagnosis and confirms ovariohysterectomy as an effective treatment for pyometra in dogs.